THE IMPROVEMENT OF STUDENT LEARNING OUTCOMES IN CLASS XII AKL 1 AGAINST FINANCIAL ACCOUNTING LESSONS BY MEANS OF IMPLEMENTATION OF DISCUSSION LEARNING METHODS AT SMK NEGERI 1 SUBANG - SITI MARYAM (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2020)
The learning objectives will be successfully determined by many factors, one of the prominent factor is the implementation of teaching and learning process by the teacher, as the teacher can directly influence, foster and enhance students' intelligence and skills. To overcome the above mentioned issue in order to achieve educational objectives to the fullest, the teacher's role is highly substantial and it is expected that the teacher provides a proper teaching method or model and is able to choose the suitable learning model in accordance with the concepts of the subject to be delivered. This research utilizes the so called Action Research within two cycles. Each cycle consists of four stages, namely design, activity and observation, reflection and revision. The targets of this study are the 12th grade students of class AKL 1 at SMK Negeri 1 Subang in the academic year of 2019/2020. The data are obtained in form of formative test results, observation sheets of teaching and learning activities. Based on the analysis results, it is concluded that student achievement has increased from cycle I to cycle II, namely cycle I (63.89%), and cycle II (94.44%). The conclusion of this Action Research is that the discussion method can positively influence the learning motivation of the 12th grade students of class AKL 1 at SMK Negeri 1 Subang in the academic year of 2019/2020, furthermore this method can be be utilized as an alternative learning method in Financial Accounting subjects.